On the relation between trade and democratization - Martin Hoppe (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
Whether trade can achieve societal change is a contested topic and difficult to investigate. This round-up aims at summarizing recent empirical research on this topic while focusing on democracy and democratization as an important part of societal change. No robust results for change arising from trade can be found, but there exists an inverse causality, i.e., democratization leading to more trade. Further, reciprocal causality between democratic consolidation and trade agreements is found, meaning an influence of democratic instability on free trade agreements and vice versa.
Keywords: 330; Außenhandel; Demokratisierung; Kausalanalyse; Theorie